Evaluasi Kinerja Pabrik Kelapa Sawit Dalam Produksi Energi Terbaharukan - Santoso, Arif Dwi (Jurnal Teknologi Lingkungan, 2018)
ABSTRACTSeveral alternative waste management innovations from oil palm mills with a capacity of 30 tons / year have been evaluated. These waste innovations are based on the most optimal renewable energy yield produced by oil palm mills, ie biogas, compost and pellets. The evaluation stage begins by collecting data from the operations of the common palm oil factories that is used as the data base-line. Furthermore, preliminary data is compared with the data of waste management innovation which is grouped into 3 (three) activities: (1) compost production from empty bunches, (2) biogas production from liquid waste treatment and (3) pellet production. The comparative results state that the plant's ability to process 1 ton of fresh fruit bunches can produce alternative renewable energy products either 207 kg of compost or 125 kWh of electricity or 125 kg pellets. This paper aims to evaluate the performance of palm oil mills in renewable energy production that is the most optimal in generating the largest profit margin. The results showed that based on the maximum profit potential obtained from each process of waste management, the percentage of the processed waste is about 19.8; 45.5 and 34.6% for the respective compost, biogas and pellet production. The processed waste will earn profit from renewable energy products of compost, biogas and pellet of as many as 6.1; 31.3 and 54.47 US$ / ton respectively. The overall waste treatment requires operating cost of 2.34 US $/ton and will result in a total profit of 91.89 US $ / ton.Keywords: waste, palm oil mill, renewable energy, performance evaluationABSTRAKBeberapa alternatif inovasi pengelolaan limbah dari pabrik kelapa sawit dengan kapasitas 30 ton/tahun telah dievaluasi. Alternatif inovasi limbah ini didasarkan pada hasil akhir energi terbarukan yang paling optimal yang dihasilkan oleh pabrik kelapa sawit, yakni berupa biogas, kompos dan pelet. Tahapan evaluasi diawali dengan mengumpulkan data kegiatan operasional pabrik kelapa sawit yang dijadikan sebagai data base line. Selanjutnya data awal tersebut dikomparasi dengan data inovasi pengelolaan limbah yang terbagi dalam kegiatan: (1) produksi kompos dari tandan kosong, (2) produksi biogas dari pengolahan limbah cair dan (3) produksi pellet. Hasil komparasi menyatakan bahwa kemampuan pabrik dalam mengolah 1 ton tandan buah segar dapat menghasilkan beberapa alternatif produk energi terbarukan yakni 207 kg kompos atau 125 kwh listrik atau 125 kg pellet. Tulisan ini bertujuan untuk membandingkan produktifitas inovasi produksi energi terbarukan yang paling optimal dalam menghasilkan margin keuntungan yang paling besar. Hasil penelitian menyatakan bahwa berdasarkan pada potensi keuntungan maksimal yang diperoleh dari masing masih proses pengelolaan limbah maka prosentase limbah yang diolah adalah dengan prosentase 19,8%; 45,5% dan 34,6%. Prosesntase limbah yang diolah tersebut akan menghasilkan produk energi terbarukan berupa kompos, biogas dan pellet dengan nilai keuntungan sebesar 6,1; 31,3 dan 54,47 US$/ton. Keseluruhan pengolahan limbah membutuhkan biaya operasional sebesar 2,34 US$ dan akan menghasilkan total keuntungan sebesar 91.89 US$/ton.Kata kunci : limbah, pabrik kelapa sawit, energi terbarukan, evaluasi kinerja